Pengaruh Bauran Pemasaran Product dan People Terhadap Keputusan Pembelian Paket Umroh Di PT. Satria Barokah Wisata - Ronal Andrianto (Politeknik Pariwisata NHI Bandung, 2023)
Based on research conducted by 2016, the results show that purchasing decisions are influenced by the product and people marketing mix by 8% and 17%. However, the characteristics of the Umrah package purchase decision are different from other products. Umrah packages have different characteristics from other products because they are related to the goal to be achieved, namely worship so that consumers consider many things before deciding to use an Umrah package product. This study aims to examine the effect caused by product variables and people variables on the purchase decision of the umroh package at PT. Satria Barokah Wisata. This research was conducted with a quantitative approach by distributing questionnaires to 260 pilgrims at PT. Satria Barokah Wisata from 2022 that has used the Umrah package by using purposive sampling technique. The theory used is the theory of travel packages from Nuriata (2014), theories about the ability of employees from Mangkunegara (2010) and purchasing decision theory from Kotler & Keller (2002). The results of the study explained that the product and people significantly influence the decision to purchase an Umrah package at PT. Satria Barokah Wisata amounted to 72.9% while the remaining 27.1% was influenced by other variables, which were not examined in this study. Thus the need for special attention from the Umrah travel organizer company, especially PT. Satria Barokah Wisata in paying attention to the product marketing mix and people to influence consumer purchasing decisions to choose the products they offer. With this result, it is hoped that it will become an opportunity for PT. Satria Barokah Wisata to optimize other promotion channels to increase sales.